Matthew Edel, Elliot D. Sclar y Daniel Luria. Shaky palaces : homeownership and social mobility in Boston’s suburbanization. Nueva York : Columbia University Press, 1984. 459 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1988)
MATTHEW EDEL, ELLIOT D. SCLAR y DANIEL LURIA, Shaky Palaces, Homeownership and Social Mobility in Boston Suburbanization, Columbia University Press, Nueva York, 1984.